Content Validation of a Political Competence Scale in Graduate Nursing Education - Delene Volkert; Claire McKinley Yoder; Lisa Robinson; Heidi Johnston; Ashley Goar (Nursing Education Perspectives, 2026)
AIM To examine the content validity of an adapted Political Competence Scale for Nurses (PCS-N) for use in graduate nursing education. BACKGROUND Instruments to evaluate political competence as a graduate-level educational outcome remain limited. METHOD Experts rated item relevance using a four-point scale (1 = not relevant to 4 = highly relevant). Scale-level indices were calculated using the average method (S-CVI/Ave). RESULTS All subscales demonstrated strong content validity, with S-CVI/Ave values ranging from 0.89 to 0.95. Mean item-level content validity index values were 0.89 for Political Knowledge, 0.94 for Political Efficacy, 0.95 for Political Interaction, and 0.91 for Political Activity. The overall scale content validity (S-CVI/Ave) was 0.92, indicating excellent scale validity. CONCLUSION Findings support the content validity and relevance of the adapted instrument for graduate nursing education. The instrument provides a foundation for national psychometric testing and may support future competency-based evaluation of graduate nursing programs.